Antioxidant Activity, Molecular Docking, Quantum Studies and In Vivo Antinociceptive Activity of Sulfonamides Derived From Carvacrol - de Oliveira, Aldo S.; Llanes, Luana C.; Nunes, Ricardo J.; Nucci-Martins, Catharina; de Souza, Anacleto S.; Palomino-Salcedo, David L.; Dávila-Rodríguez, María J.; Ferreira, Leonardo L. G.; Santos, Adair R. S.; Andricopulo, Adriano D. (Frontiers in Pharmacology, 2021)
The synthesis and antioxidant, antinociceptive and antiedematogenic activities of sulfonamides derived from carvacrol – a druglike natural product – are reported. The compounds showed promising antioxidant activity, and sulfonamide derived from morpholine (S1) demonstrated excellent antinociceptive and antiedematogenic activities, with no sedation or motor impairment. The mechanism that underlies the carvacrol and derived sulfonamides’ relieving effects on pain has not yet been fully elucidated, however, this study shows that the antinociceptive activity can be partially mediated by the antagonism of glutamatergic signaling. Compound S1 presented promising efficacy and was predicted to have an appropriate medicinal chemistry profile. Thus, derivative S1 is an interesting starting point for the design of new leads for the treatment of pain and associated inflammation and prooxidative conditions.